A coordinated control for voltage and transient stability of multi-machine power grids relying on wind energy. (July 2019) - Morshed, Mohammad Javad; Sardoueinasab, Zahra; Fekih, Afef
Highlights: Introduce a new nonlinear coordination method based on zero dynamics (ZD) approach. Design a super twisting sliding mode control to improve performance of ZD method. Coordinate controllers of DFIG and STATCOM in multi-machine power systems. Enhance transient and voltage stability of inter-connected power systems. Abstract: This paper proposes a new nonlinear control approach to coordinate doubly fed induction generator (DFIG)-based wind turbines and static synchronous compensator (STATCOM) controllers in multi-machine power systems. Its main objectives are to improve the transient and voltage stability of the inter-connected multi-machine power system via simultaneous design of the voltage of the DFIGs' rotors and reference current of STATCOM. The nonlinear approach is based on a multi input-multi output (MIMO) zero dynamics (ZD) technique augmented by a super twisting sliding mode control (STSMC) to reduce the effects of the linearization error. The proposed approach was implemented to the Kundur's four-machine two-area power system and the IEEE 39-bus power system. Its performance was assessed in the presence of various faulty scenarios and disturbances. The effectiveness of the proposed approach (ZD-STSMC) was evaluated via eigenvalue analysis, transient simulations and transient stability margin analysis (by critical clearing time (CCT)). The merits of the proposed design are further compared to those of the exact feedback linearization (EFL) approach. Enhancing the power and voltage stability of large scale power systems, damping power oscillations and providing faster post-fault recovery time are among the positive features of the proposed approach.